Design and Simulation of a Compact Filtenna for 5G Mid-Band Applications - Juma'a, Fatimah K.; Alnahwi, Falih M. (Iraqi Journal for Electrical and Electronic Engineering, 2021)
In order to provide an efficient, low cost, and small size radiating structure that passes a certain frequency band with negligible amount of interference, the combination of filters and antennas is proposed to form a single element called filtenna. This paper presents a filtenna element with compact size that can radiates in the 5G mid-band frequency range (3.6-3.8 GHz) and perfectly rejects all the frequencies outside this range. The filtenna is composed of a printed circuit antenna that is terminated with a crescent shaped stub that is coupled electromagnetically with a miniaturized sharp band-pass filter. The simulation results show a filtenna reflection coefficient with a reduced value within the intended 5G band and with high values along the other unwanted frequencies. Moreover, the structure has an omnidirectional pattern with reasonable gain value within the band of interest, and this makes the antenna very suitable for portable 5G devices.